Communication as Structural Intervention - Yohanes Damaiko Udu; Falentina Bengan Ola; Fransiskus Nala Kartijo Udu (Jurnal Communio : Jurnal Jurusan Ilmu Komunikasi, 2026)
Human trafficking in East Nusa Tenggara (NTT), Indonesia, remains a critical human rights issue shaped by both criminal practices and structural inequalities. This study examines anti-trafficking advocacy through communication practices and develops a context-sensitive framework for more effective interventions. Based on a qualitative single-case study conducted between May to November 2025, drawing on interviews with grassroots activists, participant observation, and insights from trafficking survivors, the findings reveal that anti-trafficking communication is deeply embedded in local cultural contexts – utilizing Indigenous languages, customary authorities, and community trust networks. However, these efforts remain constrained by limited communication infrastructure, resource shortages, and fragmented institutional coordination. Although storytelling is effective in raising awareness, its impact is limited without structural support. The study concludes that communication should be seen as a structural intervention linked to broader socio-economic reforms, and recommends culturally grounded, participatory, and multi-channel strategies alongside improved infrastructure and institutional coordination.